2009
DOI: 10.1080/10715760903159154
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training provides cardioprotection via a reduction in reactive oxygen species in rats submitted to myocardial infarction induced by isoproterenol

Abstract: Exercise training has demonstrated cardioprotection effects. However, the exact mechanism behind this effect is not is clear. The present study evaluated the effects of 12 weeks of previous treadmill training on the levels of oxidative damage, antioxidant enzyme activity and injury in the myocardium of rats submitted to infarction induced by isoproterenol (ISO). Isoproterenol treatment (80 mg/kg given over 2 days in two equal doses) caused arrhythmias and 60% mortality within 24 h of the last injection in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
1
24
0
3
Order By: Relevance
“…2A). Such result is surprising, since numerous studies point to the effect of physical exercise on the modulation of this enzyme in the skeletal muscle (Pinho et al, 2006; and cardiac muscle (Silva et al, 2011;Frederico et al, 2009). Therefore, this finding lends robustness to the hypothesis that the decrease in free radical production, especially superoxide, is more closely related to the effects of training on oxidative metabolism in muscle than on SOD modulation in animals that suffered myocardial infarction.…”
Section: Groupssupporting
confidence: 54%
See 1 more Smart Citation
“…2A). Such result is surprising, since numerous studies point to the effect of physical exercise on the modulation of this enzyme in the skeletal muscle (Pinho et al, 2006; and cardiac muscle (Silva et al, 2011;Frederico et al, 2009). Therefore, this finding lends robustness to the hypothesis that the decrease in free radical production, especially superoxide, is more closely related to the effects of training on oxidative metabolism in muscle than on SOD modulation in animals that suffered myocardial infarction.…”
Section: Groupssupporting
confidence: 54%
“…Recent evidence suggests that excessively reactive production of oxygen species and the resulting intensification of oxidative stress induce the occurrence of structural as well as functional damage, with dire negative consequences for cardiac recovery after AMI, as elegantly discussed in previous reviews (Grieve et al, 2004;Lee et al, 2011). But several studies have underlined the positive role of physical exercise in this recovery process and in cardioprotection (Frederico et al, 2009;Lennon et al, 2004;Nunes et al, 2008;Xu et al, 2010).…”
Section: Groupsmentioning
confidence: 94%
“…Our findings confirm the results of several studies that found a reduction in oxidative stress parameters after similar training programs (three times a week) 14,23 . The reduction of oxidative damage induced by physical training may be explained by at least three main mechanisms: first, the increase of both the expression 12 and the activity 9 of antioxidant enzymes; second, the reduction of oxidant production 13 and, also, the lower electron leakage from mitochondria 9 ; and third, the chronic exposure of tissue to ROS, induced by training, which makes the organ more resistant to the effects that derive from the mechanisms of oxidative stress 10 . ROS may affect amino acids in chain reactions by means of protein aggregates susceptible to proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings might be applicable to human beings as there is a link between the different animal species and data found in animal studies may be extrapolated to the human species. Silva et al 5 and Frederico et al 12 demonstrated that eight weeks of training with five weekly sessions was enough to reduce oxidative stress in the liver and the heart 5,12 . However, it is not known whether frequencies of two and three weekly session during eight weeks of training are sufficient to also induce improvements in OS parameters in liver and heart tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation